"There is a gorilla holding a key on the book cover": Young children's known picture book search strategies. (25th June 2021) - Wang, Pianran; Ma, Yue; Xie, Huan; Wang, Hanqing; Lu, Jinyi; Xu, Jianhua
Abstract: There is no information search system can assist young children's known picture book search needs since the information is not organized according to their cognitive abilities and needs. Therefore, this study explored young children's known picture book search strategies and extracted picture book search elements by simulating a search scenario and playing a picture book search game. The study found 29 elements children used to search for known picture books. Then, these elements are classified into three dimensions: The first dimension is the concept category of an element. The second dimension is an element's status in the story. The third dimension indicates where an element appears in a picture book. Additionally, it revealed a young children's general search strategy: Children first use auditory elements that they hear from the adults during reading. After receiving error returns, they add visual elements that they see by themselves in picture books. The findings can not only help to understand young children's known‐item search and reformulation strategies during searching but also provide theoretical support for the development of a picture book information organization schema in the search system.